2014
DOI: 10.1155/2014/578323
|View full text |Cite
|
Sign up to set email alerts
|

Test Anxiety Levels of Board Exam Going Students in Tamil Nadu, India

Abstract: The latest report by the National Crime Records Bureau has positioned Tamil Nadu as the Indian state with highest suicide rate. At least in part, this is happening due to exam pressure among adolescents, emphasizing the imperative need to understand the pattern of anxiety and various factors contributing to it among students. The present study was conducted to analyze the level of state anxiety among board exam attending school students in Tamil Nadu, India. A group of 100 students containing 50 boys and 50 gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
4
10
0
1
Order By: Relevance
“…In addition, we went for exploring possible correlation between exam anxiety status and students' level of depression. We found that majority of students have moderate to high test anxiety, while moderates to sever depression was present among more than 50% of the students.These findings are in line with similar results from similar studies [24, 25]. Students' high level of exam anxiety or depression are attributable to many factors: the third year of secondary education in Sudan is the determining year of students' future career path; students perceive this year as very important determinant of their future life opportunities.Other factors of parental and teacher expectations, latent academic and personal disabilities, perceived pressers of community expectations and fear of not meeting self-expectations are also Of remarkable probability in causing such high levels of exam anxiety and depression among students [26-28].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we went for exploring possible correlation between exam anxiety status and students' level of depression. We found that majority of students have moderate to high test anxiety, while moderates to sever depression was present among more than 50% of the students.These findings are in line with similar results from similar studies [24, 25]. Students' high level of exam anxiety or depression are attributable to many factors: the third year of secondary education in Sudan is the determining year of students' future career path; students perceive this year as very important determinant of their future life opportunities.Other factors of parental and teacher expectations, latent academic and personal disabilities, perceived pressers of community expectations and fear of not meeting self-expectations are also Of remarkable probability in causing such high levels of exam anxiety and depression among students [26-28].…”
Section: Discussionsupporting
confidence: 90%
“…The constructed Examination Anxiety Scale (EAS) efficiently assesses the examination anxiety of adolescent students because it has high internal consistency reliability (Cronbach's alpha correlation coefficient 0.764), high test-retest reliability (0.801) and excellent split-half reliability (0.767) In this study, the norms show that 16% of students belong to the high examination anxiety group, 66% of students in the average examination anxiety group, and 18 % in the low examination anxiety group. This result stands nearly similar to the findings of Mary et al (2014). In their study, they found that 8% of students remain in the high examination anxiety category, 74 % of students remain in the average examination anxiety category, and 18 % of students in the low examination anxiety category.…”
Section: Discussionsupporting
confidence: 86%
“…Media houses would be aware that reports on such deaths would resonate strongly with readers. Student suicides are a major and topical policy issue in India, frequently located within discussions around the fierce competition for student places and an accompanying intensity of exam pressure 31. Reporting on this issue will likely be of great interest to parents, who may carry a level of fear around this happening to their own children.…”
Section: Discussionmentioning
confidence: 99%